Polylactide Used as Filment in 3D Printing – Part 1: FTIR, DRIFT and TG-DTG Studies - Grabowska, Beata; Kaczmarska, Karolina; Cukrowicz, Sylwia; Mączka, Elżbieta; Bobrowski, Artur (Journal of Casting & Materials Engineering, 2020)
A short literature review was undertaken in terms of the structure, properties and applications of polymers, including those commonly used in 3D printing. The research part included the structural and thermal analysis of polylactide (PLA), which is an example of an extensively used polymer in the developing 3D technology. Special attention was paid to the comparison of structure and thermal stability of two different (from various producers) polylactide samples. The research, involving such analytical methods as infrared spectroscopy (FTIR) and diffuse reflectance infrared spectroscopy (DRIFT), allowed the comparison of the structure of the two PLA samples considered. The determination of the temperature range in which changes related to PLA thermodestruction occur was a result of the performed thermoanalytical research (DRIFT, TG-DTG). Thermal studies also allowed to establish the temperature range in which the material does not yet degrade, which is important in the context of future planned research work on polylactide modification to obtain the improvement of the thermal and mechanical properties of PLA-based materials. This research area will be described in the second part of the publication.